Implementation E-Module Physics Base I Based Kvisoft Flipbook Maker - Karti, Karti; Damayanti, Roza (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2015)
The development of this e-module was motivated by students' difficulties in understanding particle dynamics material. This research aims to produce a Basic Physics I e-module on particle dynamics and to determine student perceptions of the Basic Physics I e-module on particle dynamics that was developed. This type of research is (research and development) with the ADDIE development model which includes analysis, design, development, implementation and evaluation. The subjects of this research were 2016 PGMIPA-U Physics Education students at Jambi University. The research instruments used were media expert validation questionnaires, material expert validation questionnaires and student perception questionnaires. The results of the questionnaire trial showed that there were 16 valid statements and one invalid statement. The reliability value obtained was 0.898 in the very high category. Furthermore, the results of research on student perceptions obtained data covering 3 aspects, namely aspects in the good category. Based on the results obtained in the research, it can be concluded that the development of an e-module for Basic Physics I material on particle dynamics based on kvisoft flipbook maker is very suitable for use as a teaching material in the Basic Physics I subject on particle dynamics at Jambi University